Abrupt shear thickening of aqueous solutions of hydrophobically modified poly(N,N `-dimethylacrylamide-co-acrylic acid) - Lele, Ashish K.; Shedge, Aarti; Badiger, Manohar V.; Wadgaonkar, Prakash; Chassenieux, Christophe (Macromolecules, 2010)
We report some new and interesting observations on the abrupt and large shear-induced thickening of aqueous solutions of hydrophobically modified poly(N,N'-dimethylacrylamide-co-acrylic acid). High molecular weight copolymer was prepared by free radical copolymerization of N,N'-dimethylacrylamide [DMA] and acrylic acid [AA] and was subsequently modified to different extents using a hydrophobic compound, namely, 3-pentadecylcyclohexylamine [3-PDCA], which is derived from a renewable resource material, cashew nutshell liquid [CNSL]. The structural elucidation of the base copolymer and the hydrophobically modified copolymers was performed by (1)H and (13)C NMR spectroscopy. The zero shear viscosities [eta(0)] of the hydrophobically modified polymers were lower than that of the precursor poly(N,N'-dimethylacrylamide-co-acrylic acid) until some critical polymer concentration, which increased with increase in hydrophobic modification. Above the critical concentrations, the eta(0) of the hydrophobically modified copolymers surpassed that of the precursor at the same concentration. At moderate shear rates some of these hydrophobically modified copolymers exhibited an abrupt shear-induced thickening in which the viscosity of the samples increased severalfold. We show here from creep experiments that thickening occurs only when the shear rate reaches a critical value, (gamma) over dot(crit), and that the thickened samples can be trapped in different metastable states by controlling the applied stress. Interestingly, the shear thickened samples showed further thickening upon decreasing the applied stress. Eventually, the metastable samples revert to their equilibrium states at characteristic time that depends on (small) probe stress.